2020
DOI: 10.2807/1560-7917.es.2020.25.38.1900716
|View full text |Cite
|
Sign up to set email alerts
|

Rabies vaccination strategies in the Netherlands in 2018: a cost evaluation

Abstract: Background: The risk of contracting rabies is low for travellers. However, the number of Dutch travellers potentially exposed abroad following an animal-associated injury and needing post-exposure prophylaxis (PEP) has increased, resulting in increased costs. Aim: Here, we evaluated the costs and the cost-effectiveness of different pre-and post-exposure interventions in the Netherlands, taking into account the 2018 World Health Organization (WHO) recommendations for the prevention of rabies. Methods: A decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Health is more than absence of disease, it encompasses a wide range of contexts that cannot be expressed in money [ 36 ], emphasising the importance of health-related QOL (HR-QOL). Suijkerbuijk et al [ 18 ] published a cost–benefit analysis for different rabies vaccination strategies in the Netherlands, but were unable to incorporate the cost implications in terms of HR-QOL. Such cost implications would be a valuable addition to the determination of health in contemporary society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health is more than absence of disease, it encompasses a wide range of contexts that cannot be expressed in money [ 36 ], emphasising the importance of health-related QOL (HR-QOL). Suijkerbuijk et al [ 18 ] published a cost–benefit analysis for different rabies vaccination strategies in the Netherlands, but were unable to incorporate the cost implications in terms of HR-QOL. Such cost implications would be a valuable addition to the determination of health in contemporary society.…”
Section: Discussionmentioning
confidence: 99%
“…Intuitively, a higher PrEP uptake seems a reasonable strategy to reduce risk of infection and consequent anxiety and distress. A recent cost evaluation of different rabies vaccination strategies in the Netherlands by Suijkerbuijk et al [ 18 ] concluded, in contrast, that a higher PrEP uptake would result in higher overall costs. However, only material costs were analysed, while loss of quality of life was not taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of rabies immunoglobulin used, the type of rabies vaccination administered, and the location of delivery, such as intramuscular or intradermal administration, all affect subsequent treatment expenses ( Haradanhalli et al , 2022 ). The rabies victims are responsible for paying for other expenses including travel, lodging, and hospitalization, but in the veterinary field, the community often pays for dog vaccinations ( Suijkerbuijk et al , 2020 ). The veterinary and medical sectors are equally responsible for the costs of rabies control and prevention ( Subedi et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies show the failure to give protective antibody levels in human serum by RIG injected IM. 13,14 RIG is in limited supply all over the world and only wound infiltration would not only save costs, 15,16 but also spare up to 60% of RIG volume for India 17 and other countries where RIG is not available. 18 Animal model studies have clearly shown that any amount of RIG given IM is of no use as no effective titers of antibodies (i.e.…”
Section: Introductionmentioning
confidence: 99%